1996
DOI: 10.1071/zo9960047
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Relationships Within Australasian Waterfowl (Anseriformes)

Abstract: Within Australia there are 19 endemic species of Anseriformes. Six of these belong to monotypic genera, some of which remain controversial with respect to phylogenetic relationships. Sequence variation in a 307base pair fragment of the cytochrome-b gene was compared from 23 species of waterfowl (the Cairina sequence was obtained from the literature) to elucidate further the relationships of these monotypic Australian genera. Anseranas and Dendrocygna were identified as the earliest diverged genera among the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 27 publications
7
42
1
Order By: Relevance
“…Moreover, the coracoids of Malacorhynchus are very similar to those of Mionetta, especially in the presence of a distinct depression on the ventral surface of the blade (contra Livezey 1996b), also shared with Stictonetta. This indicates support for the primitive location of Malacorhynchus advocated by Sraml et al (1996). Livezey (1986) found Malacorhynchus to be a highly derived tadornine but in a more extensive analysis (Livezey 1996b) found its placement unresolved.…”
Section: Anseriformesmentioning
confidence: 91%
See 3 more Smart Citations
“…Moreover, the coracoids of Malacorhynchus are very similar to those of Mionetta, especially in the presence of a distinct depression on the ventral surface of the blade (contra Livezey 1996b), also shared with Stictonetta. This indicates support for the primitive location of Malacorhynchus advocated by Sraml et al (1996). Livezey (1986) found Malacorhynchus to be a highly derived tadornine but in a more extensive analysis (Livezey 1996b) found its placement unresolved.…”
Section: Anseriformesmentioning
confidence: 91%
“…Sraml et al (1996) found that, based on a strict consensus tree of mitochondrial DNA data, Malacorhynchus was the sister taxa to Biziura and close to Dendrocygna. When we examined the skeletal characters of the humerus of both M. membranaceus and M. scarletti, we found that they both have all the diagnostic features of the Dendrocheninae as given in Livezey & Martin (1988) and as discussed herein, and differ in no appreciable way.…”
Section: Anseriformesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ducks, together with the ostrich, emu, peacock, turkey, quail, and other birds, play a major role in studies of bird evolution. Up to now, most available molecular data concerning ducks have come from evolutionary studies based on the analysis of mitochondrial DNA sequence (Cooper et al 1996;Liu et al 1996;Sraml et al 1996;Sorenson 1998, 1999;Donne-Gousse et al 2002). However, information about genetic markers in the duck is limited (Buchholz et al 1998;Maak et al 2000Maak et al , 2003Paulus and Tiedemann 2003;Stai and Hughes 2003;Huang et al 2005).…”
mentioning
confidence: 99%